Psychoanalysis and Education: a possible treatment for school complaints - Nádia Laguárdia de Lima; Ronaldo Sales de Araújo; Eduardo Pio de Souza; Allana Fernanda Gonçalves Dias; Carolina Albuquerque Barbosa; Raquel Gonçalves Silveira Alves; Karina Maciel Nihari; Nayara Serrano Barcelos Marchi (Universidade Federal do Rio Grande do Sul, 2015)
This paper presents a theoretical reflection on a study conducted with elementary school teachers in a public school. It was applied Psychoanalytic orientation on conversations as a work methodology, supported by ethics of desire and accountability. The conversations had a main theme, which consisted on the difficulties confronted by teachers in their teaching practice. Teachers have elected three main deadlocks over their educational practice: family, sexuality and public policies. Based on Speech Theory and Temporal Triad proposed by Lacan - instant of seeing, time of understanding and moment of concluding - the author brings up a reflection on speech offer effects on elementary school teachers in a public school.